PENERAPAN MODEL ROLE PLAYING DENGAN MEDIA MINI DRAMA TERHADAP PEMAHAMAN SISWA PADA MATERI ZAKAT FITRAH - Fitriandini Wijayanti, Risqi; Kholil, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fiqh learning on the topic of zakat al-fitr in Madrasah Ibtidaiyah is still frequently conducted using conventional lecture-based methods, which tend to result in low student participation and limited understanding. This study aims to: (1) describe the implementation process of the role-playing learning model assisted by mini-drama media in teaching the topic of zakat al-fitr, (2) examine the level of understanding of fifth-grade students after participating in learning activities using this model and media, and (3) identify the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach. The research subjects consisted of 26 fifth-grade students, one fiqh teacher, and the principal of MI Al–Islamiyah Karanganyar Paiton as supporting informants. Data were collected through observation, interviews, and documentation. The data were analyzed using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the role-playing model supported by mini-drama media was carried out systematically through several stages, including planning, role-playing activities, discussion, and reflection. The learning process became more active, interactive, and engaging, which contributed to improving students’ understanding of zakat al-fitr material in both cognitive and affective aspects. Most students were able to clearly re-explain the concept of zakat al-fitr, its rules and regulations, and its practical implementation. The main supporting factors were students’ enthusiasm and strong support from the teacher, while the inhibiting factors included limited instructional time and students’ lack of self-confidence at the beginning of the learning process. This study concludes that the role-playing learning model supported by mini-drama media is effective in enhancing students’ understanding of zakat al-fitr material. The implication of this research highlights the importance of teachers being more creative in selecting innovative learning models. Furthermore, future researchers are recommended to examine the effectiveness of this model in other fiqh learning topics.